Malaysia Humanitarian Logistics: A Successful Collaboration in Humanitarian Relief Works Between NGOs in Malaysia - Malik, Hisyam (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2022)
Humanitarian organisations find it incredibly challenging to work with a diverse group of stakeholders. Coordination between actors is challenging, and occasionally efforts are duplicated. Collaboration issues have been identified as a major stumbling block in the management of humanitarian projects. These issues must be addressed since they will lead to inefficiency and impede the humanitarian response process before, during, and after a disaster. This research explores the Malaysian humanitarian logistics scenario as well as the factors that influence successful collaboration in humanitarian relief efforts between Malaysian NGOs. In this study, the researcher adopted qualitative methods and interviewed four NGOs involved in humanitarian work in the year 2020, allowing the researcher to investigate differences within and across humanitarian efforts. This study found the main pillars of successful collaboration in humanitarian works, such as communication, coordination and trust, which influence the process of collaboration and help all crisis management stakeholders understand their roles and responsibilities in providing humanitarian aid.